Reproductive Development of Verutus volvingentis (Tylenchida Heteroderidae) - Esser, R P (Journal of nematology, 1983)
Verutus volvingentis Esser, 1981 deposits eggs in the rhizosphere without a gelatinous matrix. Ecdysis was not observed to occur in the egg. Spicular primordia in the rectal area of a second-stage larva were well defined. One larva increased in width from 28.2 mum to a maximum of 51.7 mum after 176.5 hours of feeding, prior to the second ecdysis. It then decreased steadily in width to 33.3 mum, at which time it had molted to a fully developed male. Males leave the third-stage larval integument embedded in the root following final ecdysis. The unique feature of female development was the occurrence of large vaginal primordial cells. Male and female development took from 6 to 15 days and 17 days, respectively